A facile and green procedure in preparing dibenzo-chromeno-phenazine-diones using an effectual and recyclable Brønsted acidic ionic liquid - Chou-Yi Hsu; Riyadh Abdulkareem; Harikumar Pallathadka; Vikrant Abbot; Mamata Chahar; Dilsora Abduvalieva; Yasser Fakri Mustafa; Usama S. Altimari; Abeer mhussan jabbar; Ahmed Hussein Zwamel (Scientific Reports)
Abstract First, a Brønsted acid ionic liquid (BAIL) in the role of a double acid-base called 1,3-n-propyl-bipyridinium bisulfonic acid-ditrifluoroacetate (PBPBSDT) was produced, and its skeleton was determined via TGA, mass, 13C NMR, 19F NMR, 1H NMR and FT-IR data. Further, it was successfully applied in the preparation of dibenzo-chromeno-phenazine-dione derivatives (1a-12a, 9–15 min, 90–98%) via one-pot multicomponent domino reaction among 2 mmol 2-hydroxynaphthalene-1,4-dione, 1 mmol benzene-1,2-diamine, and 1 mmol aldehydes under optimal conditions (5 mol% of PBPBSDT, solvent-free, 60 °C). The proper reproducibility of the PBPBSDT homogeneous catalyst (5 times), solvent-free medium, reasonable TON (Turnover Number) and TOF (Turnover Frequency) numbers, the non-metallic framework of the catalyst, and the formation of C-N, C = N, C-C, C = C, C-O bonds in a single operation are the distinct advantages of this protocol.